Affirming the Abuse Liability and Addiction Potential of Menthol: Differences in Subjective Appeal to Smoking Menthol Versus Non-Menthol Cigarettes Across African American and White Young Adult Smokers. Issue 1 (18th August 2021) - Cohn, Amy M; Alexander, Adam C; Ehlke, Sarah J
Abstract: Introduction: Menthol cigarettes are popular among young adults and are disproportionately used by African American smokers. Menthol's minty and cooling sensations have been hypothesized to enhance the appeal and reinforcement of smoking; however, differences in menthol's subjective appeal across races have been inconsistent. This secondary data analysis examined differences in subjective appeal for smoking menthol versus non-menthol cigarettes between African American and White young adult smokers. Methods: Young adults (ages 18–24) recruited from Amazon Mechanical Turk (December 2018–January 2019) completed an online survey of tobacco use behavior. Past year smokers ( n = 1726) answered questions about subjective responses to smoking (reward, satisfaction, throat hit, craving reduction, and aversion). Results: Significantly more African American (73.2%) compared to White (52.4%) smokers preferred menthol cigarettes ( p < .001). Menthol smokers reported greater positive and negative subjective responses to smoking than non-menthol smokers. Positive and negative subjective response were both associated with greater smoking intensity and lower cigarette harm perceptions. Interactions of menthol preference and race on indices of subjective appeal also emerged. African American non-menthol smokers reported lower levels of satisfaction, reward, and craving reduction compared to White non-menthol smokers. Conclusions: The relationship between menthol preference and subjective response to smoking differs by race. Menthol is rated as more appealing than non-menthol smoking, and appeal indices were linked to smoking intensity and lower harm perceptions, indicating greater abuse liability of menthol cigarettes. Policies that ban menthol cigarettes may have a particularly positive impact on the cigarette smoking of African American young adult smokers. Implications: The FDA issued an Advanced Notice of Proposed Rule Making to examine the role menthol in tobacco products to inform regulations to restrict or ban flavors. This study showed that menthol smokers reported greater appeal to smoking than non-menthol smokers; and an interaction of race x menthol preference showed African American non-menthol smokers reported the lowest levels of appeal to smoking. Multiple indices of cigarette appeal were positively correlated with smoking intensity and lower cigarette harm perceptions, highlighting the addiction potential of menthol cigarettes. Findings suggest a menthol cigarette ban could help reduce tobacco use among young adults.